2007
DOI: 10.1111/j.1750-3841.2007.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Sensory Analysis of Organically and Conventionally Grown Vegetables

Abstract: Consumers of organically grown fruits and vegetables often believe that these products taste better than conventional produce. However, comparison of produce from supermarket shelves does not permit adequate assessment of this consumer perception, given potentially confounding cultivar and environmental effects. We used replicated side-by-side plots to produce organic and conventional vegetables for consumer sensory studies. In one test, red loose leaf lettuce, spinach, arugula, and mustard greens, grown organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 19 publications
11
80
1
4
Order By: Relevance
“…Thompson and Kidwell (1998), reported that taste, resembling that of home-grown produce and other quality considerations as important motivations for buying organic food. Most studies have shown that many buyers of organically produced vegetables accept as true that organic vegetables taste better than conventionally produced vegetables (Fillion and Arazi, 2002;Zhao et al, 2007) though sensory evaluation might have proven otherwise. Availability of safe vegetables affected the willingness of consumer to pay higher prices for vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and Kidwell (1998), reported that taste, resembling that of home-grown produce and other quality considerations as important motivations for buying organic food. Most studies have shown that many buyers of organically produced vegetables accept as true that organic vegetables taste better than conventionally produced vegetables (Fillion and Arazi, 2002;Zhao et al, 2007) though sensory evaluation might have proven otherwise. Availability of safe vegetables affected the willingness of consumer to pay higher prices for vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Schifferstein & Oude Ophuis (1998) find out that health was an important motivator for buying organic foods for "incidental" organic buyers in the Netherlands, whereas both health and environmental concerns were regarded by "regular" buyers. Perceptions about organic foods remain the same; that they are healthy, beneficial for the environment and taste good or better than conventional foods (Lea & Worsley, 2005;Padel & Foster, 2005;Zhao et al, 2007). Consumers interested in the organic food industry are also worried about pesticides and growth hormones in food.…”
Section: Introductionmentioning
confidence: 98%
“…Consumers were concerned over paying high prices for the imported organic vegetables that does not match with its freshness and quality. A study conducted in the U.S (Zhao, Chambers, Matta, Loughin & Carey 2007) has shown that there were no significant differences between organic and conventional vegetables in terms of 'consumer perceived' sensory quality. In view of the different perspectives onthe relationship between product attributes and customers' perceived value of organic food, the following hypothesis will be tested in this respect: H 1 Product attributes has a positive influence on the consumers' perceived value of organic food.…”
Section: Product Attributesmentioning
confidence: 99%